Entre common et commons : penser / dire / imaginer la communauté avec / après Raymond Williams - Catherine Bernard (Contextes)
The categories of the “common” and of “community” feature among the terms listed in Raymond Williams’ 1976 essay Keywords; and although the category of the “commons” is not strictly synonymous with Williams’ keywords of “common” and “community” as he defined and revisited them throughout his career, it is enlightening to fathom how Williams’ concepts enter in a dialogue with recent explorations of the notions of “community” and of the “commons”. The genealogy the article traces links Williams’ concepts to that of the community fashioned by Maurice Blanchot and Jean-Luc Nancy, then by Roberto Esposito in his 1998 essay Communitas, and Michael Hardt and Antonio Negri in Multitude. War and Democracy in the Age of Empire (2004) and Commonwealth (2009). Via such a genealogy, the article explores what these concepts tell us of a body politic in the making and of its imagined possibles.